L-Carnitine Enhances Axonal Plasticity and Improves White-Matter Lesions after Chronic Hypoperfusion in Rat Brain. Issue 3 (March 2015) - Ueno, Yuji; Koike, Masato; Shimada, Yoshiaki; Shimura, Hideki; Hira, Kenichiro; Tanaka, Ryota; Uchiyama, Yasuo; Hattori, Nobutaka; Urabe, Takao
Chronic cerebral hypoperfusion causes white-matter lesions (WMLs) with oxidative stress and cognitive impairment. However, the biologic mechanisms that regulate axonal plasticity under chronic cerebral hypoperfusion have not been fully investigated. Here, we investigated whether L-carnitine, an antioxidant agent, enhances axonal plasticity and oligodendrocyte expression, and explored the signaling pathways that mediate axonal plasticity in a rat chronic hypoperfusion model. Adult male Wistar rats subjected to ligation of the bilateral common carotid arteries (LBCCA) were treated with or without L-carnitine. L-carnitine-treated rats exhibited significantly reduced escape latency in the Morris water maze task at 28 days after chronic hypoperfusion. Western blot analysis indicated that L-carnitine increased levels of phosphorylated high-molecular weight neurofilament (pNFH), concurrent with a reduction in phosphorylated phosphatase tensin homolog deleted on chromosome 10 (PTEN), and increased phosphorylated Akt and mammalian target of rapamycin (mTOR) at 28 days after chronic hypoperfusion. L-carnitine reduced lipid peroxidation and oxidative DNA damage, and enhanced oligodendrocyte marker expression and myelin sheath thickness after chronic hypoperfusion. L-carnitine regulates the PTEN/Akt/mTOR signaling pathway, and enhances axonal plasticity while concurrently ameliorating oxidative stress and increasing oligodendrocyte myelination of axons, thereby improving WMLs and cognitive impairment in a rat chronic hypoperfusion model.